2022
DOI: 10.3390/ijms23031525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Parameters of In Vitro Static Tensile Strain on Human Periodontal Ligament Cells Simulating the Tension Side of Orthodontic Tooth Movement

Abstract: This study aimed to investigate the effects of different magnitudes and durations of static tensile strain on human periodontal ligament cells (hPDLCs), focusing on osteogenesis, mechanosensing and inflammation. Static tensile strain magnitudes of 0%, 3%, 6%, 10%, 15% and 20% were applied to hPDLCs for 1, 2 and 3 days. Cell viability was confirmed via live/dead cell staining. Reference genes were tested by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) and assessed. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“… 49 Increased osteogenesis is usually accompanied by lower levels of inflammatory cytokines and chemokines. 10 , 50 , 51 Accordingly, in the present study, with increasing frequency, the osteogenic commitment increased, and the suppression of pro-inflammatory genes and the relative inflammatory response pathway were observed.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“… 49 Increased osteogenesis is usually accompanied by lower levels of inflammatory cytokines and chemokines. 10 , 50 , 51 Accordingly, in the present study, with increasing frequency, the osteogenic commitment increased, and the suppression of pro-inflammatory genes and the relative inflammatory response pathway were observed.…”
Section: Discussionsupporting
confidence: 62%
“…The effects of different tensile force magnitudes and durations have been investigated in some studies. Among the magnitudes, a magnitude of 10% generally led to a lower level of inflammation and a higher level of osteogenesis, 10 whereas a magnitude of 12% was found to correlate well with strain conditions at the mid-root under physiological loading conditions 11 , 12 and to induce optimal effects in both the proliferation and osteogenesis of PDLSCs. 13 Cyclic tension alone at 3000 μstrain significantly enhanced SATB Homeobox 2 (Satb2) after 3 h of loading and significantly upregulated Runx2 after 6 h. 14 The synthesis of BMP9 increased under 6-h continuously applied cyclic tension.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, our results support previous studies, emphasizing the importance of working below the mechanical force overload threshold (20% strain) to prevent hydrogel rupture. [3,[62][63][64][65] The same condition (10% strain, 1 h per day) sustained stretching as a determining factor for triggering cell proliferation and ECM remodeling. [3,66] Importantly, the numerical simulations of the stretching hydrogel under this optimal strain of 10% evidenced that the cells experienced stresses up to 280 Pa in magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…[1] OTM is a remodeling process in which the application of a force induces bone resorption on the compression side and bone apposition on the tension side, that is, between the periodontal ligament (PDL) and alveolar bone. [2,3] PDL is a connective tissue that lies between the cementum covering the root of the tooth and alveolar bone. It firmly anchors the tooth to alveolar bone via Sharpey's fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different mechanical parameters, including magnitude and frequency, on the osteogenic differentiation of PDLSCs under tension have been studied. Among different magnitudes, a magnitude of 10% was investigated to lead to a lower level of inflammation and a higher level of osteogenesis [35], and a magnitude of 12% was considered to correlate well with strain conditions at the mid-root under physiological loading conditions [36] and induce optimal effects in both the proliferation and osteogenesis of PDLSCs [37]. In our previous study, we have compared the effects of different frequencies on the osteogenic differentiation of PDLSCs at the magnitude of 12% and found that 0.7 Hz most significantly promoted the osteogenesis of PDLSCs among different frequencies [38].…”
Section: Discussionmentioning
confidence: 99%